STUDENTS' DATA INTERPRETATION SKILLS IN GENERAL BIOLOGY LABS: ANALYSIS BASED ON PRIOR KNOWLEDGE AND IMPLICATIONS FOR SCIENTIFIC LITERACY - Aziza Karenina; Nuris Fattahillah; Andyta Ma'rifatul Usnia; Winda Rachman Putri; Rasyid Zuhdi; Angsoka Dwipayana Marthaliakirana (INSECTA: Integrative Science Education and Teaching Activity Journal, 2026)
Data interpretation ability is an important component of scientific literacy that needs to be developed through practicum activities. Prior knowledge acts as a cognitive basis that enables students to understand scientific concepts, recognize experimental variables, and connect observation results with relevant theories in biology practical activities. This study aims to analyze differences in students' data interpretation abilities in General Biology practicums and examine the relationship between prior knowledge and data interpretation abilities from a scientific literacy perspective. This study is quantitative with a descriptive, comparative, and correlational design. The subjects were students in classes A, B, C, and D who participated in General Biology practicums. Prior knowledge data were obtained through a pretest, while data interpretation abilities were obtained through practicum results. Data analysis was carried out using normality tests, homogeneity tests, One Way ANOVA tests, Tukey Post Hoc follow-up tests, and Pearson correlation tests. The results showed that significant differences occurred between class D and classes A, B, and C, while there were no significant differences between classes A, B, and C. The results of the Pearson correlation test showed a significant positive relationship between prior knowledge and data interpretation abilities (r = 0.62; p < 0.05), which is included in the moderate to strong category. The practical implications of this study emphasize the importance of considering prior knowledge in teaching biology practicums through pre-learning activities and providing scaffolding during the practicum, so that students' data interpretation skills can develop optimally and support increased scientific literacy.